Internalisasi Nilai Pendidikan Islami dalam Kisah Luqman Al-Hakim dan Relevansinya terhadap Pendidikan Islam di Era Desrupsi - Nur Kholidah Nasution (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2021)
The Qur'an is a guidence for Muslims as well as a miracle for all mankind. As a guideline it contains ideal values that can be implemented in a ideal systems. One of the values contained in the Quran is reflected through the story of Luqman al-Hakim who detailed the story of a man named Luqman who conveyed wisdom to his son. This wisdom has relevance to Islamic education and its implementation in life today. This research is qualitative-descriptive research. This study seeks to answer how the reflection of the value of Islamic education that can be internalized by society in the era of disruption with the characteristics of the development of science and technology but suffered a moral setback or moral deandence. The values of education that can be internalized and contain ideal educational values as contained in the story of Luqman al-Hakim are advice, moral education and religious education.